Analysis of Work Posture Using the Rapid Upper Limb Assessment (RULA) Method for Garbage Bank Employee: Completion of Posture with RULA - Syahreen Nurmutia; wahyu madeali (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2023)
In the industrial world the use of human power is still dominant, especially manual material handling activities (Manual Material Handling or abbreviated as MMH). In addition, MMH when compared with the use of materials using assistive devices is the flexibility of movement that can be done for light loads. In using MMH activities identified as a major risk as the main cause of low back pain. This study aims to minimize work posture complaints in waste banks, seen from how the procedure for positioning work postures properly so as to minimize the level of injury to workers. By using the Rapid Upper Limb Assessment (RULA) method. The work postures produced in this study carried out the work of moving goods to the scales and obtained a final score of 6, which means changing work postures so that they are better for workers